Proceedings. The 21st Digital Avionics Systems Conference
DOI: 10.1109/dasc.2002.1052983
|View full text |Cite
|
Sign up to set email alerts
|

Real-time integrity monitoring of stored geo-spatial data using forward-looking remote sensing technology [aircraft navigation/displays]

Abstract: Terrain Awareness and Warning Systems (TAWS) and Synthetic Vision Systems (SVS) provide pilots with displays of stored geo-spatial data (e.g. terrain, obstacles, and/or features). As comprehensive validation is impractical, these databases typically have no quantifiable level of integrity. This lack of a quantifiable integrity level is one of the constraints that has limited categories: Controlled Flight Into Terrain (CFIT) and Loss of Control in flight (LOC) are focal points of both agency's initiatives. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…An experimental X-band weather radar -This forward-looking version of the monitor was not integrated with the flight deck displays, but was evaluated from an experimenter's workstation in the aft cabin. This concept and preliminary results of post-flight analysis can be found in [12].…”
Section: Database Integrity Monitoring Equipmentmentioning
confidence: 97%
See 1 more Smart Citation
“…An experimental X-band weather radar -This forward-looking version of the monitor was not integrated with the flight deck displays, but was evaluated from an experimenter's workstation in the aft cabin. This concept and preliminary results of post-flight analysis can be found in [12].…”
Section: Database Integrity Monitoring Equipmentmentioning
confidence: 97%
“…11,12,13 While DIME performance is critical to SVS, this flight test evaluated, for the first time, a proposed pilot-vehicle interface for indicating a database integrity alert.…”
Section: Dime Performancementioning
confidence: 99%
“…In many cases the image will be so compelling that the pilot will be slow to detect a problem with the terrain database, so other integrity checks are needed. NASA and others have evaluated a number of integrity monitoring schemes 6,7,8,9 and reported that the detection and warnings are effective.…”
Section: Video Content Challenges -Svsmentioning
confidence: 98%
“…Methods do include direct and indirect evaluation of the sensor outputs such using terrain database to monitor the integrity of synthetic vision systems [6] and using forward-looking remote sensors to monitor the integrity of stored geo-spatial data [7]. Other methods include the integration of the two information sources in a complementary manner, GNSS and IRS for example, and evaluation via a screening test of the innovations (on a per measurement basis).…”
Section: Hazard and Integrity Monitormentioning
confidence: 99%